Efficacy and tolerability of oxycodone versus fentanyl for intravenous patient-controlled analgesia after gastrointestinal laparotomy: A prospective, randomized, double-blind study. Issue 39 (September 2016) - Ding, Zhen; Wang, Kaiguo; Wang, Baosheng; Zhou, Naibao; Li, Hao; Yan, Bo
Abstract: Background: It has been suggested that oxycodone is effective in relieving acute postoperative pain. The aim of this study was to investigate the efficacy and tolerability of oxycodone (O) versus fentanyl (F), and the adequate potency ratio of oxycodone and fentanyl in patients with intravenous patient-controlled analgesia after gastric laparotomy. Methods: In this double-blinded, randomized, controlled study, 60 patients undergoing elective gastric laparotomy were allocated to receive either oxycodone or fentanyl for postoperative intravenous patient-controlled analgesia (potency ratio 60:1). The patients received ketorolac 60 mg before the end of anesthesia and then continued with patient-controlled analgesia for 48 hours postsurgery. Pain severity, side effects and respiration rate were recorded 30 minutes, 3, 6, 12, 24, and 48 hours after the surgery. Cumulative opioid requirements and patient satisfaction were also measured. Results: The median consumption more than 48 hours after operation of oxycodone was 50 mg (range: 40.0–62.4 mg) and fentanyl was 0.8 mg (range: 0.6–1.1 mg), and the percentage of patients requiring rescue medication was not statistically significant. Numeric rating scores at rest and upon movement were significantly lower in group O than in F ( P < 0.05). Whereas the incidences of adverse events were similar between the groups (33.3% vs 27.6%, P = 0.64), a significant higher sedation scores were found in patients given fentanyl at 30 minutes after the surgery ( P = 0.04). Conclusion: Oxycodone was comparable to fentanyl in the relief of postoperative pain following gastric laparotomy. Oxycodone not only provides better postoperative pain relief and less sedation, but also there was a tendency toward more side effects with oxycodone.